An experimental study on the pathophysiology of rectal prolapse [Rektal prolapların patofizyolojisi üzerine deneysel bir çalışma] - YEGEN, BERRAK (Bilimsel Tip Yayinevi, 2021)
Objective: For decades, rectal prolapse has been hypothesized to be caused due to laxity or weakness of the pelvic floor muscles which is often supposed to be related to childbearing in females. However, 50% of females with rectal prolapse have been reported to be nulliparous and this hypothesis does not explain the incidence of rectal prolapse in males. The aim of this study was to evaluate the role of rectal redundancy in rectal prolapse pathophysiology. Material and Methods: Nineteen female Sprague Dawley rats (250-300 g) at 16 weeks of age were obtained from the animal center. Rats were divided into two groups as rectal mobilization (study) group (n= 9) and sham-operated control (n= 10) group. In the study group, soft dissection was applied and rectum were mobilized up from the pelvic floor to create a redundant or hypermobilized rectum.The primary outcome was the rate of rectal prolapse after rectal mobilization. Results: As compared to the sham-operated control group, in which none of the rats had rectal prolapse throughout the post-surgical period, rectal prolapse was observed in four of the rats in the rectal mobilization group (0% vs. 44%; p= 0.006). Being unable to increase the length of the rectums of the rats, but using only mobilization to create the redundancy, and the lack of data regarding any adhesions after surgery are the main limitations of this study. Conclusion: This study showed the role of rectal redundancy on the rectal prolapse pathophysiology. © 2021 Bilimsel Tip Yayinevi. All rights reserved.
Keywords: Pathophysiology; Rectal prolapse; Redundancy